Role of carotid duplex in the assessment of carotid artery restenosis after endarterectomy or stenting - Szegedi, István; Potvorszki, Fanni; Mészáros, Zsófia Réka; Daniel, Cecilia; Csiba, László; Oláh, László (Frontiers in Neurology, 2023)
Introduction Redo carotid endarterectomy (CEA) and carotid stenting (CAS) are often performed when there is evidence of post-procedural restenosis. The incidence of restenosis after carotid reconstruction is not negligible, ranging from 5 to 33%. The diagnosis of significant internal carotid artery (ICA) restenosis is usually based on duplex ultrasound (US) criteria, mostly on peak-systolic flow velocity (PSV). However, there have been no generally accepted duplex US criteria for carotid restenosis after CAS or CEA. Methods In this systematic review, the PubMed/ Medline and Scopus databases were screened to find trials that reported duplex US criteria for significant restenosis after CEA and/or CAS. Only those reports were analyzed in which the restenoses were also assessed by CT/MR or digital subtraction angiography as comparators for duplex US. Results Fourteen studies met the predetermined search criteria and were included in this review. In most studies, PSV thresholds for significant in-stent ICA restenosis after CAS were higher than those for significant stenosis in non-procedurally treated (native) ICA. Many fewer studies investigated the US criteria for ICA restenosis after CEA. Despite the heterogeneous data, there is a consensus to use higher flow velocity thresholds for assessment of stenosis in stented ICA than in native ICA; however, there have been insufficient data about the flow velocity criteria for significant restenosis after CEA. Although the flow velocity thresholds for restenosis after CAS and CEA seem to be different, the large studies used the same duplex criteria to define restenosis after the two procedures. Moreover, different studies used different flow velocity thresholds to define ICA restenosis, leading to variable restenosis rates. Discussion We conclude that (1) further examinations are warranted to determine appropriate duplex US criteria for restenosis after CAS and CEA, (2) single duplex US parameter cannot be used to reliably determine the degree of ICA restenosis, (3) inappropriate US criteria used in large studies may have led to false restenosis rates, and (4) studies are required to determine if there is a benefit from redo carotid artery procedure, such as redo-CEA or redo-CAS, starting with prospective risk stratification studies using current best practice non-invasive care alone.